El crecimiento de las pequeñas empresas confeccionistas en Lima, 1980-1997: la formación de redes sociales y redes estratégicas - Mendoza Gallo, Oscar Alberto (1999)
The objective of the present study is the small firm. Particularly, those who have sustainable accumulation capacity through time. Our research was meant to find out the factors that have influenced in the growth of these firms and which are the internal and external interrelations that made possible this growth. We also wanted to know how in a social and economic crisis · context, some migrants with limited resources had a sustainable economic growth and became successful managers.